The study of public awareness towards Sihat Malaysia / Siti Nurhafizah Adam Suboh - Adam Suboh, Siti Nurhafizah (2010)
This research conducted focusing on the “The Study of Public Awareness towards Sihat Malaysia at Kuala Lumpur”. Since a medical card is quite important nowadays, customer awareness is very important to ensure the awareness level of Sihat Malaysia in term of promotional mix is high. The main objectives are (1) to identify the level of public awareness towards Sihat Malaysia, (2) to determine the most effective elements of promotional mix towards creating public awareness towards Sihat Malaysia and (3) to provide recommendations that can improve the level of public awareness towards Sihat Malaysia. The respondents of this study were public in Kuala Lumpur area. 70 questionnaires had been distributed among them. The researcher had used convenience sampling as the sampling technique. The process of analyzing and interpreting data has been presented by tables and figures using method of analysis such as reliability analysis, frequency analysis and descriptive analysis. The result shows that the level of public awareness towards Sihat Malaysia is moderate. The recommendations are the insurance company may improve the level of awareness towards Sihat Malaysia by putting heavier emphasis on public relation and the advertising efforts are maintained, if not improved.